The lifespan retrieval of the most important, the happiest, and the saddest autobiographical memories - Ekinci, Emine Öykü. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
In the present study, we examined the reminiscence bump and the phenomenological characteristics of outstanding life experiences, and tested the applicability of the bump accounts. Additionally, we investigated the content and narrative quality of their memories. Adults aged above 40 were asked to report in detail their most important, happiest, and saddest autobiographical memories. Results showed that most important and happiest memories formed a broad bump covering the 20-39 interval. Saddest memories generated a discernable bump in 30-49. Regarding the phenomenological characteristics, the bump memories were only higher in expectedness than memories from other life periods. The events mentioned in most important and happiest memories overlapped with Turkish cultural life-script to a great extent. Most important memories occurred within 20-29 matched the life-script more than the memories from other periods. While most important and happiest memories were mostly on relationships and achievements, saddest memories largely had life-threatening content. The memory narratives were quite specific, while they did not include much integrative statements. Participants aged between 40-49 reported more specific saddest memories than the other age groups. Age groups did not differ in terms of integration of memories.
Keywords: Autobiographical memory.